Theoretical and Practical Explorations of Information Design and Persuasion: Research Contributions of Professor Zhao Xiaoquan to Health Communication - Zhou, Wenqing (The Journal of Medicine, Humanity and Media, 2026)
Professor Zhao Xiaoquan currently serves as a professor at George Mason University and Editor-in-Chief of the international top-tier journal Health Communication. As a leading scholar in the field of health communication, he earned his doctoral degree from the Annenberg School for Communication at the University of Pennsylvania, and possesses both a solid academic foundation and practical experience in tobacco regulation at the U.S. Food and Drug Administration (FDA). His research follows a coherent logical thread of “audience cognition → information design → behavior change,” with key focuses on three thematic areas: tobacco control and health communication campaigns, COVID-19 pandemic information communication, and general health communication. Employing diverse research methods (e.g., large-scale national survey data, experimental methods, interview methods), his work systematically explores the laws and intervention effects of information design across different public health scenarios, and deeply reveals the health information cognitive characteristics and behavioral decision-making mechanisms of specific populations such as adolescents, ethnic minorities, and patients with chronic diseases. His research findings have provided direct scientific evidence and practical guidance for practical initiatives, including the FDA’s national tobacco control education campaigns and information management in public health emergencies. Professor Zhao’s research is characterized by strong logical consistency, a distinct practical orientation, and diverse methodologies. It has promoted the two-way interdisciplinary empowerment of communication studies and public health, and constructed a multi-dimensional research framework covering “routine-emergency” and “general-special” contexts. This article systematically sorts out his representative research achievements over the past 15 years, clarifies his academic ideas and research characteristics, analyzes his academic contributions and practical implications, and accordingly points out potential directions for future research.